Condom use and incarceration among STI clinic attendees in the Deep South. (December 2016) - Brinkley-Rubinstein, Lauren; Parker, Sharon; Gjelsvik, Annie; Mena, Leandro; Chan, Philip; Harvey, Julia; Marshall, Brandon; Beckwith, Curt; Rose, Jennifer; Riggins, Reginald; Arnold, Trisha; Nunn, Amy
Abstract Background Incarceration history is associated with lower rates of condom use and increased HIV risk. Less is known about duration of incarceration and multiple incarcerations' impact on condom use post-release. Methods In the current study, we surveyed 1, 416 adults in Mississippi about their incarceration history and sexual risk behaviors. Generalized estimating equations (GEE) were used to test associations between duration of incarceration, multiple incarcerations, socio-demographic factors, substance use, sexual behavior, and event level condom use at last sex. Results After adjusting for covariates, having been incarcerated for at least 6 months two or more times remained significantly associated with condomless sex. Conclusions This study found a strong, independent relationship between condom use and multiple, long-term incarceration events among patients in an urban STI clinic in the Deep South. The results suggest that duration of incarceration and multiple incarcerations have significant effects on sexual risk behaviors, underscoring the deleterious impact of long prison or jail sentences on population health. Our findings also suggest that correctional health care professionals and post-release providers might consider offering comprehensive sexual and reproductive health services and those providing community care should consider screening for previous incarceration as a marker of risk.